2014
DOI: 10.1007/s12013-014-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Brachial-Ankle Pulse Wave Velocity, Carotid Artery Intima-Media Thickness, Ankle-Brachial Index, and the Severity of Coronary Lesions

Abstract: Coronary angiography is the gold standard for the diagnosis of coronary artery disease. Coronary artery Gensini scoring systems measure both the extent and the degree of stenosis of coronary artery and therefore, give clinicians a more accurate, objective, and comprehensive assessment of the severity of coronary artery disease. Using Gensini scoring systems in combination with statistical analysis, we found that five variables, namely, Brachial-ankle pulse wave velocity (PWV), ankle-brachial index (ABI), carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…43 Carotid artery atherosclerosis is also a predictor of cardiovascular events in patients with hypertension. 44 At the same time, CIMT measurements are a noninvasive test used to assess the presence of subclinical atherosclerosis, 45 but the ultrasonic resolution is based on the operator's experience and technical skill levels. Therefore, the operator's experience and technical skill levels were associated with errors and have great influence on diagnosis, which meant many patients out from early detection, diagnosis and reatment of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…43 Carotid artery atherosclerosis is also a predictor of cardiovascular events in patients with hypertension. 44 At the same time, CIMT measurements are a noninvasive test used to assess the presence of subclinical atherosclerosis, 45 but the ultrasonic resolution is based on the operator's experience and technical skill levels. Therefore, the operator's experience and technical skill levels were associated with errors and have great influence on diagnosis, which meant many patients out from early detection, diagnosis and reatment of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that CIMT is an independent predictor of coronary atherosclerosis load in symptomatic intermediate risk patients (15). Zuo et al (27) have shown that CIMT is associated with the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Markers of endothelial function, such as brachial artery flow-mediated dilation (FMD) and the reactive hyperemia index (RHI), 11,12 as well as other markers of vascular function, are also used to assess subclinical CVD in research settings. 13 Erectile dysfunction (ED) is a common disorder with an overall prevalence of around 18% in men aged 20 or more years. 14 The proportion of ED by cause has not been well described in the literature.…”
Section: The Relationship Of Erectile Dysfunction and Subclinical Carmentioning
confidence: 99%